Staged use of ordinal and linear disability scales: a practical approach to granular assessment of acute stroke outcome - Chaisinanunkul, Napasri; Starkman, Sidney; Gornbein, Jeffrey; Hamilton, Scott; Chatfield, Fiona; Conwit, Robin; Saver, Jeffrey L. (Frontiers in Neurology, 2023)
Background The modified Rankin Scale (mRS) assessment of global disability is the most common primary endpoint in acute stroke trials but lacks granularity (7 broad levels) and is ordinal (scale levels unknown distances apart), which constrains study power. Disability scales that are linear and continuous may better discriminate outcomes, but computerized administration in stroke patients is challenging. We, therefore, undertook to develop a staged use of an ordinal followed by a linear scale practical to use in multicenter trials. Methods Consecutive patients undergoing 3-month final visits in the NIH FAST-MAG phase 3 trial were assessed with the mRS followed by 15 mRS level-specific yes–no items of the Academic Medical Center Linear Disability Score (ALDS), a linear disability scale derived using item response theory. Results Among 55 patients, aged 71.2 (SD ± 14.2), 67% were men and the entry NIHSS was 10.7 (SD ± 9.5). At 90 days, the median mRS score was 3 (IQR, 1–4), and the median ALDS score was 78.8 (IQR, 3.3–100). ALDS scores correlated strongly with 90 days outcome measures, including the Barthel Index (r = 0.92), NIHSS (r = 0.87), and mRS (r = 0.94). ALDS scores also correlated modestly with entry NIHSS (r = 0.38). At 90 days, the ALDS showed greater scale granularity than the mRS, with fewer patients with identical values, 1.9 (SD ± 3.2) vs. 8.0 (SD ± 3.6), p < 0.001. When treatment effect magnitudes were small to moderate, projected trial sample size requirements were 2–12-fold lower when the ALDS rather than the mRS was used as the primary trial endpoint. Conclusion Among patients enrolled in an acute neuroprotective stroke trial, the ALDS showed strong convergent validity and superior discrimination characteristics compared with the modified Rankin Scale and increased projected trial power to detect clinically meaningful treatment benefits.